Symbolic Representation and Cultural Meaning in Culinary Vocabulary Processed Marine Products in Anyer Beach Ecoturism Area - Rosidin, Odien; Hasani, Aceng (International Proceedings of Nusantara Raya, 2022)
From a linguistic perspective, traditional food or local culinary processed seafood traded in the Anyer Beach tourist area is an interesting phenomenon and is important to study in depth. The culinary name represents a rich symbolic form with a unique cultural meaning. This article discusses lingual units and cultural meanings in naming seafood processed culinary at the Anyer Beach tourist attraction. This article was produced through an in-depth study using qualitative methods using an anthropolinguistic theory approach. Data was collected by means of participant observation and in-depth interviews with recording techniques. The data is classified and analyzed according to the focus of the problem that has been formulated and interpreted according to the situational context and cultural context. The results of this study indicate that the lingual units used in naming the processed seafood are the Sundanese lexicon and the Banten dialect of the Javanese language in the category of words and phrases. The lexicon embodies cultural meanings that represent the ecosystem and life of a typical coastal community.